Epidemiology of carbapenemase-producing Enterobacterales in England, May 2015–March 2019: national enhanced surveillance findings and approach. Issue 3 (September 2020) - Freeman, Rachel; Ironmonger, Dean; Hopkins, Katie L.; Puleston, Richard; Staves, Peter; Hope, Russell; Muller-Pebody, Berit; Brown, Colin S.; Hopkins, Susan; Johnson, Alan P.; Woodford, Neil; Oliver, Isabel
Summary: Background: In response to increasing numbers of carbapenemase-producing Enterobacterales (CPE) in England, Public Health England (PHE) launched an electronic reporting system (ERS) for the enhanced surveillance of carbapenemase-producing Gram-negative bacteria. Our study aimed to describe system engagement and the epidemiology of CPE in England. Methods: Engagement with the ERS was assessed by calculating the proportion of referrals submitted this system. ERS data were extracted and cases defined as patients with CPE isolated from a screening or clinical specimen in England between 1 st May 2015 to 31 st March 2019. Descriptive summary statistics for each variable were prepared. Results: The ERS processed 12, 656 suspected CPE reports. Uptake of the ERS by local microbiology laboratories varied, with approximately 70% of referrals made via the ERS by April 2016; this steadily decreased after March 2018. Six-thousand eight-hundred and fifty-seven cases were included in the analysis. Most cases were from colonised patients (80.6%) rather than infected, and the majority were inpatients in acute hospital settings (87.3%). Carbapenemases were most frequently detected in Klebsiella pneumoniae (39.1%) and Escherichia coli (30.3%). The most frequently identified carbapenemase families were OXA-48-like (45.1%) and KPC (26.4%). Enhanced data variables were poorly completed. Conclusions: The ERS has provided some insight into the epidemiology of CPE in England. An increasing number of routine diagnostic laboratories have introduced methods to routinely identify acquired carbapenemases and PHE has modified its approach to ensure robust surveillance, which is an essential aspect of an effective response to prevent and control the spread of CPE.